Fraud Prevention Analysis: Perceptions of Bank Sumsel-Babel Employees - Putra, Berry; Adam, Mohamad; Meutia, Inten (Jurnal Ilmu Ekonomi Terapan, 2023)
If a nation's financial statements are stable and exist, and the financial system is stable, banking companies can contribute to economic growth. The growth or development of the banking world is not only dominated by certain banks such as BUMN Banks or Private Banks. However, this is also experienced by Regional Development Banks. In several cases in banking, Fraud occurs due to internal processes (human error), system failures, or external errors. This research uses a quantitative research method with a questionnaire observation approach, with the object respondents being Bank Sumsel-Babel employees, totaling 238 respondents and 34 question instruments”Smart-PLS analysis technique. Of the 32 indicators (2 indicators omitted), in the outer measurement model, data has validity and reliability with the approach that has been achieved. At the same time, in the inner path coefficient test model, all variables are negative with a value <- 420 (weak category). Meanwhile, at the R-square level of 0.688 (moderate), it can create a goodness of fit, robust value, and an accuracy of 95.0%. The estimation results show that all variables have a negative direction coefficient that significantly affects compensation, competence, and internal control of Fraud. At the same time, organizational culture, with a value of 0.138 > 0.05, indicates no effect on Fraud.